Association of sociodemographic and environmental factors with the mental health status among preschool children-Results from a cross-sectional study in Bavaria, Germany - Zach, Angelika; Meyer, Nicole; Hendrowarsito, Lana; Kolb, Stefanie; Bolte, Gabriele; Nennstiel-Ratzel, Uta; Stilianakis, Nikolaos; Herr, Caroline (International Journal of Hygiene and Environmental Health, 2016)
It has been reported that a great proportion of mental health disorders have an origin in early childhood. In order to evaluate factors possibly associated with children's health, the health monitoring units have been established since 2004 in six study regions in Bavaria, Germany. The second health monitoring survey, implemented in 2005-06, focuses on the mental health status of preschool children. The goal of this study is (1) to examine the association of sociodemographic and environmental factors with mental health and (2) to analyze the applicability of the results of the health monitoring units to all preschool children in Bavaria by calculating weighting factors.Data on 6206 preschool children are available. Logistic regression analysis is applied to analyze possible associations with mental health. A weighting method is applied to correct for deviances compared to the whole population of preschool children in Bavaria (N=132,783).11% of preschool children show mental health problems. Regarding different indicators of sociodemographic status, low household income [unadjusted OR 3.34, 95% CI: 2.23-4.98] shows the strongest association of mental health problems. Non-accessibility of green space [unadjusted OR 2.74, 95% CI: 1.87-4.00] is also strongly associated with mental health. The results of the unweighted and weighted analysis are similar.Our findings suggest that sociodemographic status and factors in the living environment show associations with mental health of children. Based on the results of the unweighted and weighted analyses, the second health monitoring analysis shows little deviances compared to data of all Bavarian preschool children. Therefore, the results can be compared to all Bavarian preschool children.
EVALuna2:5552